Health-related quality of life and economic burden of chronic lymphocytic leukemia in the era of novel targeted agents. (1st September 2020) - Waweru, Catherine; Kaur, Simarjeet; Sharma, Sheetal; Mishra, Namita
Abstract: Objective: To quantify the health-related quality of life (HRQoL) and economic burden of chronic lymphocytic leukemia (CLL). Methods: Studies were searched through Embase, MEDLINE, PubMed, and Cochrane Library, as well as conference abstracts (1 January 2000–2 June 2019). Results: Overall, 12 and 17 primary studies were included in the HRQoL and economic burden reviews, respectively. Patients with CLL reported impairment in various quality of life domains when compared with healthy controls, including fatigue, anxiety, physical functioning, social functioning, depression, sleep disturbance, and pain interference. Key factors associated with a negative impact on the HRQoL burden of CLL included female gender, increased disease severity, and the initiation of multiple lines of therapy. Economic burden was assessed for patients with CLL based on disease status and the treatment regimen received. The main cost drivers related to CLL were outpatient and hospitalization-related costs, primarily incurred as a result of chemo/chemoimmunotherapy, adverse events (AEs), and disease progression. Treatment with targeted agents, i.e. ibrutinib and venetoclax, was associated with lower medical costs than chemoimmunotherapy, although ibrutinib was associated with some increased AE costs related to cardiac toxicities. Cost studies of targeted agents were limited by short follow-up times that did not capture the full scope of treatment costs. Conclusions: CLL imposes a significant HRQoL and economic burden. Our systematic review shows that an unmet need persists in CLL for treatments that delay progression while minimizing AEs. Studies suggest targeted therapies may reduce the economic burden of CLL, but longer follow-up data are needed.